Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
Đào Trung Hiếu

Bài 1: Phân tích đa thức thành nhân tử

1. 5x-10-xy+2y

2.2x^2+2y^2-4xy-xz+yz

3.5x^2y-10xy^2

4.3x^2-6xy+3y^2-12z^2

5.x^2+4xy-16+4y^2

6.7x-6x^2-2

7.(2x+y)^2+x(2x+y)

8.x(x-y)+5x-5y

9.x^2-y^2+2x+1

10.x^3-9x

11.xy-2y+x-2

12.x^3-3x^2-4x+12

13.3x-x^2-2xy+3y-y^2

Đào Trung Hiếu
17 tháng 10 2021 lúc 18:07

làm ơn giúp e vs

Nguyễn Hoàng Minh
17 tháng 10 2021 lúc 18:11

\(1,=\left(x-2\right)\left(5-y\right)\\ 2,=2\left(x-y\right)^2-z\left(x-y\right)=\left(x-y\right)\left(2x-2y-z\right)\\ 3,=5xy\left(x-2y\right)\\ 4,=3\left(x^2-2xy+y^2-4z^2\right)=3\left[\left(x-y\right)^2-4z^2\right]\\ =3\left(x-y-2z\right)\left(x-y+2z\right)\\ 5,=\left(x+2y\right)^2-16=\left(x+2y-4\right)\left(x+2y+4\right)\\ 6,=-\left(6x^2-3x-4x+2\right)=-\left(2x-1\right)\left(3x-2\right)\\ 7,=\left(2x+y\right)\left(2x+y+x\right)=\left(2x+y\right)\left(3x+y\right)\\ 8,=\left(x-y\right)\left(x+5\right)\\ 9,=\left(x+1\right)^2-y^2=\left(x-y+1\right)\left(x+y+1\right)\\ 10,=\left(x^2-9\right)x=x\left(x-3\right)\left(x+3\right)\\ 11,=\left(x-2\right)\left(y+1\right)\\ 12,=\left(x-3\right)\left(x^2-4\right)=\left(x-3\right)\left(x-2\right)\left(x+2\right)\\ 13,=3\left(x+y\right)-\left(x+y\right)^2=\left(x+y\right)\left(3-x-y\right)\)